2009
DOI: 10.1021/ja901262g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TMEDA on Iron-Catalyzed Coupling Reactions of ArMgX with Alkyl Halides

Abstract: A new reaction mechanism for the iron-catalyzed cross-coupling reaction of ArMgX with alkyl halides using (TMEDA)FeAr(2) and (TMEDA)Fe(Ar)Br is proposed on the basis of the isolation and reaction of these organoiron intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 28 publications
5
134
0
7
Order By: Relevance
“…[12b,d] We describe herein the effect of TMEDA on the configurational stability of a-lithiated trifluoromethyl-, chloro-, and phenylthio-substituted aryloxiranes in both coordinating and noncoordinating solvents. [14] The role of this ligand will also be tackled in light of the calculated barriers to inversion and activation parameters. A general trend becomes apparent for such reactive intermediates with a Abstract: The employment of hexane/ N,N,N',N'-tetramethylethylenediamine (TMEDA) dramatically hinders the racemization of those lithiated styrene oxides (trifluoromethyl-, chloro-, and phenylthio-substituted) that have been proven to be configurationally unstable in THF on the timescale of their re-A C H T U N G T R E N N U N G actions.…”
Section: Introductionmentioning
confidence: 99%
“…[12b,d] We describe herein the effect of TMEDA on the configurational stability of a-lithiated trifluoromethyl-, chloro-, and phenylthio-substituted aryloxiranes in both coordinating and noncoordinating solvents. [14] The role of this ligand will also be tackled in light of the calculated barriers to inversion and activation parameters. A general trend becomes apparent for such reactive intermediates with a Abstract: The employment of hexane/ N,N,N',N'-tetramethylethylenediamine (TMEDA) dramatically hinders the racemization of those lithiated styrene oxides (trifluoromethyl-, chloro-, and phenylthio-substituted) that have been proven to be configurationally unstable in THF on the timescale of their re-A C H T U N G T R E N N U N G actions.…”
Section: Introductionmentioning
confidence: 99%
“…A radical type (II) (III) mechanism has been reported for iron catalyzed cross coupling reactions of alkyl halides with arylmagnesium reagents. 52 The catalytic cycle depicted on the left hand side of Figure 3 shows a canonical (0) (II) mechanism, which consists of the oxidative addition of an aryl halide to metal(0) intermediate D, transmetalation between arylmetal halide E and Ar 1 MgX, and reductive elimination of Ar 1 Ar 2 from diarylmetal(II) F. 53 We believe that the present reaction based on the metal uoride catalyst does not take place via the popular (0) (II) mechanism, but more likely via the higher valent metalate mechanism, which is analogous to those of cuprate mediated substitution reactions and catalytic cross coupling reactions. 54 The nal reductive elimination process in …”
Section: Mechanistic Consideration Of the Catalytic Fluoridementioning
confidence: 99%
“…These results indicated that the cross-coupling reaction catalyzed by complex 1 could involve a radical mechanism in the reaction of alkyl halide with the iron species. 6b, 15,16 In our system, the slow addition of phenylmagnesium bromide to the reaction mixture is unfavorable for the formation of the cross-coupled product (Table 1). This procedure resulted in increase of the formation of biphenyl, the homocoupled product.…”
mentioning
confidence: 91%